"Healthy alliances?"--other sexual health services and their views of genitourinary medicine. Issue 6 (December 1995) - McClean, H L; Reid, M; Scoular, A
Abstract : OBJECTIVE--To assess health professionals' views of genitourinary medicine (GUM) services in a large UK city and to determine potential intervention measures for change. METHODS--A postal questionnaire was sent to 205 service providers in a range of sexual health services in Glasgow, including GUM specialist doctors, nurses and health advisers. The questionnaire included structured questions about organisation and use of GUM services, assessment of profile and stigma, and asked about factors most likely to influence future service development. RESULTS--128 questionnaires were returned from areas throughout the city. Non-GUM health professionals had poor factual knowledge about the organisation of GUM services. GUM had a poor profile compared with other sexual health services and stigma was thought to exist about the service. Most non-GUM service providers continue traditionally to regard GUM mainly as a referral centre for a few specific sexually transmitted infections and not as a centre for holistic sexual health care. Genital chlamydial infection and pelvic inflammatory disease were considered low priority for GUM referral by some groups of service providers. These views contrasted with those working in the speciality. There was generally poor professional contact between GUM and other service providers involved in sexual health. Most indicated that greater levels of information and publicity, increased professional contact, and a broader range of services within GUM were important for future service development. CONCLUSIONS--The response to the questionnaire strongly indicates that there is poor awareness of and consequently suboptimal use of the full range of services offered by GUM. Potential interventions to address this need include increased cross-speciality collaboration and targeting of specific groups of service providers involved in sexual health care. Important groups include hospital-based specialists and voluntary agencies as well as general practitioners. There is a clear need to project the broad range of sexual health services offered by GUM, and to emphasise the role of GUM in managing specific sexual health problems including several sexually transmitted infections.